Securing Tyrants or Fostering Reform? U.S. Internal Security Assistance to Repressive and Transitioning Regimes - Jones, Seth G.; Oliker, Olga; Chalk, Peter; Fair, C. Christine; Lal, Rollie (RAND Corporation, 2023)
This study examines the results of U.S. assistance to the internal security forces of four repressive states: El Salvador, Uzbekistan, Afghanistan, and Pakistan. Efforts to improve the security, human rights, and accountability of security forces appear more likely to succeed in states transitioning from repressive to democratic systems. In addition, several factors are critical for success: the duration of assistance, viability of the justice system, and support and buy-in from the local government (including key ministries).